ELMO1 Regulates RANKL-Stimulated Differentiation and Bone Resorption of Osteoclasts - Liang, Xinyue; Hou, Yafei; Han, Lijuan; Yu, Shuxiang; Zhang, Yunyun; Cao, Xiumei; Yan, Jianshe (Frontiers in Cell and Developmental Biology, 2021)
Bone homeostasis is a metabolic balance between the new bone formation by osteoblasts and old bone resorption by osteoclasts. Excessive osteoclastic bone resorption results in low bone mass, which is the major cause of bone diseases such as rheumatoid arthritis. Small GTPases Rac1 is a key regulator of osteoclast differentiation, but its exact mechanism is not fully understood. ELMO and DOCK proteins form complexes that function as guanine nucleotide exchange factors for Rac activation. Here, we report that ELMO1 plays an important role in differentiation and bone resorption of osteoclasts. Osteoclast precursors derived from bone marrow monocytes (BMMs) of Elmo1–/– mice display defective adhesion and migration during differentiation. The cells also have a reduced activation of Rac1, p38, JNK, and AKT in response to RANKL stimulation. Importantly, we show that bone erosion is alleviated in Elmo1–/– mice in a rheumatoid arthritis mouse model. Taken together, our results suggest that ELMO1, as a regulator of Rac1, regulates osteoclast differentiation and bone resorption both in vitro and in vivo.